Peran PR PT. Pegadaian (Persero) Kanwil X Bandung dalam Program Corporate Social Responsibility - Safa Camila Rahma Nur Annisa Priono; Sophia Novita (Bandung Conference Series: Public Relations, 2023)
Abstract. PT. Pegadaian (Persero) is a state-owned company engaged in the pawn business. In carrying out its corporate social responsibility, PT. Pegadaian (Persero) launched The Gade Clean and Gold program "Segregating Waste Saving Gold". Lack of public awareness of the environment, especially in waste management, is one of the factors causing the increasing amount of waste. With this program, PT. Pegadaian (Persero) seeks to improve environmental conditions and assist the government in managing waste, especially in the city of Bandung. This study uses a qualitative method with a case study approach. The purpose of this study is to determine the PR process in the CSR program The Gade Clean and Gold, the supporting and inhibiting factors of the CSR program The Gade Clean and Gold, and the reasons for PT. Pegadaian (Persero) Kanwil X Bandung chose The Gade Clean and Gold as a CSR program. The results of the research show that PR PT. Pegadaian (Persero) Kanwil X Bandung carries out a very important process in The Gade Clean and Gold program as a form of corporate concern and responsibility for the cleanliness of the surrounding environment by motivating and educating the public to sort and manage waste properly and correctly. The controlling factor is the amount of support from the community to the President of the Republic of Indonesia, while the inhibiting factor is that there are still some people who still lack concern for waste sorting. The reason for selecting the program is the mandatory program from the central Pawnshop and efforts to encourage change by helping the community and the Bandung City Government in overcoming waste problems. Abstrak. PT. Pegadaian (Persero) merupakan salah satu perusahaan BUMN yang bergerak di bidang usaha gadai. Dalam menjalankan tanggung jawab sosial perusahaannya, PT. Pegadaian (Persero) meluncurkan program The Gade Clean and Gold “Memilah Sampah Menabung Emas”. Kurangnya kesadaran masyarakat terhadap lingkungan terutama dalam pengelola sampah menjadi salah satu faktor penyebab jumlah sampah yang terus meningkat. Adanya program tersebut, PT. Pegadaian (Persero) berupaya untuk memperbaiki keadaan lingkungan hidup serta membantu pemerintah dalam mengelola sampah khususnya di Kota Bandung. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Tujuan dari penelitian ini yaitu untuk mengetahui proses PR dalam program CSR The Gade Clean and Gold, faktor pendukung dan penghambat dari program CSR The Gade Clean and Gold, serta alasan PT. Pegadaian (Persero) Kanwil X Bandung memilih The Gade Clean and Gold sebagai program CSR. Hasil penelitian menunjukkan bahwa PR PT. Pegadaian (Persero) Kanwil X Bandung melakukan proses yang sangat penting dalam program The Gade Clean and Gold sebagai bentuk kepedulian dan tanggung jawab perusahaan terhadap kebersihan lingkungan sekitar dengan memotivasi dan mengedukasi masyarakat untuk memilah dan mengelola sampah dengan dan benar. Faktor pendungnya yaitu banyaknya dukungan dari masyarakat hingga Presiden RI, sedangkan faktor penghambatnya yaitu masih terdapat beberapa masyarakat yang masih minim kepedulian terhadap pemilahan sampah. Alasan pemilihan program yaitu program wajib dari Pegadaian pusat serta upaya mendorong perubahan dengan membantu masyarakat dan Pemerintah Kota Bandung dalam mengatasi permasalahan sampah